Nano twin alloy current collector material and preparation method thereof

The nanotwin alloy liquid collector materials are prepared through vacuum smelting, high-pressure solid solution and Joule heat treatment, which solves the problems of low diffusion rate and uneven deposition of the current medium-collector materials in the prior art, and achieves efficient metal deposition and improved battery performance.

CN119890323APending Publication Date: 2025-04-25YANSHAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510083007.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing metal battery current collector materials have problems such as low diffusion rate, unsolid bonding of the modified coating, complex preparation process and high cost, which limits their application in the battery field.

Method used

The nanotwin alloy liquid collector material is prepared by vacuum smelting, high pressure solution and Joule heat treatment. The chemical composition is A-xB, where A is Al, Cu or Ni, B is Si, Ag or Sn, and x is the mass fraction of component B. The range of mass fractions is 10-15 wt.%.

Benefits of technology

It significantly improves the diffusion rate of metal on the current collector surface, improves the uniformity of metal deposition, avoids the growth of dendrites, improves the cycle stability and safety of the battery, and maintains a high reversible capacity after a long period of time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890323A_ABST
    Figure CN119890323A_ABST
Patent Text Reader

Abstract

The invention discloses a nano twin alloy current collector material and a preparation method thereof, the chemical composition expression of the nano twin alloy current collector material is A-xB, A is one of Al, Cu or Ni, B is one of Si, Ag or Sn, x is the mass fraction of the component B, and the range is 10-15 wt.%; the nano-twin alloy current collector material is prepared through vacuum melting, high-pressure solid solution and Joule heat treatment in sequence, the preparation method is simple, the process is easy to control, the production period is short, the nano-twin alloy current collector material is suitable for large-scale industrial production, and the total battery assembled by the prepared nano-twin alloy current collector material has the advantages that the total battery capacity is high; the material still has relatively high reversible capacity after long-time circulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal material preparation, and relates to a nano twin alloy current collector material and a preparation method thereof. Background Art

[0002] With the rapid growth of demand for electrochemical energy storage, researchers are advancing the development of next-generation batteries at full speed, which need to have high capacity, long-term stability and low cost. Among many technologies, metal batteries stand out due to their high energy density, but the uneven deposition of metal on the surface of the current collector in metal batteries makes it difficult to ensure safety performance. Therefore, researchers are committed to developing advanced current collector technologies. Currently, these strategies mainly include enhancing the stability of the current collector interface through coatings and constructing porous skeletons as carriers for metal deposition. These strategies aim to alleviate the problem of uneven metal deposition, but the coatings are easy to expand and separate from the current collectors, and three-dimensional porous current collectors lead to low internal space utilization efficiency.

[0003] At present, alloying has become an effective method to solve the above problems. It optimizes the alloy structure (such as grain boundaries and intermetallic compounds) through self-reconstruction and has been applied to a variety of metal battery systems. In theory, twin defects in alloys are considered to be highly stable due to their low interfacial energy. These high-density twins not only give the alloy material extremely high conductivity and mechanical strength, but also effectively reduce the energy barrier in the diffusion process, thereby achieving more uniform metal deposition.

[0004] However, the currently prepared metal battery current collector materials still have certain defects. For example, the document "ACS Applied Energy Materials 2023, 6, 4, 2140-2150" discloses a method for preparing a nano-twinned copper current collector. This method uses a finely polished titanium plate as a cathode substrate in an 8.5-liter tank. The basic electrolyte contains 1.08M CuSO4·5H2O, 25mM H2SO4, 0.7mM NaCl and thiol organic additives to control the grain orientation of the electrodeposited copper foil. Although the document successfully prepared a twinned current collector and conducted in-depth research in the field of energy storage, the mechanical properties of the twinned alloy current collector material have been reduced due to the large size of the twins.

[0005] The document "Advanced Functional Materials 2024, 2401914" discloses a heterostructure (V / VO x ) modified aluminum current collector, which was prepared by magnetron sputtering and calcination on commercial low-cost aluminum foil (V / VO x @Al) successfully developed V / VO x(x=0.2-0.5) heterostructure, the study found that vanadium and vanadium oxide have strong sodium affinity, which can effectively reduce the Na nuclear barrier, thereby preventing the formation of dendrites during Na deposition. However, due to the poor mechanical properties of the coating prepared by the magnetron sputtering scheme, the surface coating of the current collector falls off after cycling, resulting in a decrease in the cycling performance of the battery.

[0006] Chinese invention patent application No. 201510133468.2 discloses a three-dimensional porous current collector and its preparation method and use, wherein the three-dimensional porous current collector is composed of nanobeams and / or microbeams, each nanobeam or microbeam is composed of nanofibers or microfibers, and the diameter of the nanofibers or microfibers is 0.05-5um, and the three-dimensional porous current collector design can effectively inhibit the growth of dendrites of the negative electrode of metal secondary batteries, which has a significant effect on improving battery safety and life. However, although the prepared three-dimensional porous current collector material can effectively inhibit the formation of dendrites, thereby improving the safety of the metal negative electrode, the porous structure of the three-dimensional porous current collector will wear or fatigue during high stress or long-term cyclic use, affecting the battery life. In addition, since the three-dimensional porous current collector contains a large number of pores and staggered channels, it will increase the diffusion path of ions, thereby limiting the rapid transmission of ions and reducing the diffusion efficiency of ions.

[0007] Chinese invention patent application No. 201410613914.5 discloses a method for preparing a nano-twinned Cu-Al or Cu-Zn alloy, wherein the alloy is obtained by multiple processes such as solid solution, cooling, isochannel deformation, and cryogenic treatment, and the obtained alloy microstructure presents a nano-twinned lamellar structure, thereby improving the comprehensive mechanical properties of the alloy to a certain extent. However, in the field of battery current collectors, the nano-twinned lamellar structure in the alloy, compared with the nano-twinned particle structure, will cause the metal deposition to be deposited along the twinning defects at the lamellar layer, which makes the deposited metal present a linear distribution. As the capacity increases, the deposition becomes uneven, which has a negative impact on the battery performance. In addition, the method involves multiple complex processes, the preparation process is relatively cumbersome, and may increase the production cost and difficulty, which is not conducive to large-scale industrial production. Therefore, although it has improved in mechanical properties, its application in the field of battery current collectors is limited by the unevenness of metal deposition and the complexity of the process.

[0008] In summary, the main disadvantages of current metal battery current collector materials include:

[0009] 1. The diffusion rate is low, resulting in uneven deposition of metal on the surface of the current collector;

[0010] 2. The modified coating is not firmly bonded to the substrate, resulting in uneven deposition of metal on the surface of the current collector;

[0011] 3. The preparation process is complicated, not environmentally friendly, and the preparation cost is high, which is not suitable for large-scale production.

[0012] Therefore, the present application is proposed to address the shortcomings of the above-mentioned current collector materials. Summary of the invention

[0013] In view of the above technical problems, the present invention aims to provide a nano-twin alloy current collector material and a preparation method thereof. The chemical composition expression of the nano-twin alloy current collector material is A-xB, wherein A is one of Al, Cu or Ni, B is one of Si, Ag or Sn, and x is the mass fraction of the B component, ranging from 10-15wt.%; the nano-twin alloy current collector material is prepared by vacuum melting, high-pressure solid solution and Joule heat treatment in sequence. The preparation method of the present invention is simple, the process is easy to control, and the production cycle is short, so it is suitable for large-scale industrial production. The full battery assembled with the prepared nano-twin alloy current collector material still has a high reversible capacity after long-term cycling.

[0014] To achieve the above object, the technical solution adopted by the present invention is:

[0015] A nano twin alloy current collector material, the chemical composition of which is expressed as: A-xB, wherein A is one of Al, Cu or Ni, B is one of Si, Ag or Sn; x is the mass fraction of component B, ranging from 10-15wt.%.

[0016] As a limitation of a nano-twin alloy current collector material of the present invention, nanoparticles containing twin defects in the nano-twin alloy current collector material account for 65-85% of the entire nanoparticles.

[0017] The present invention also provides a method for preparing a nano twin alloy current collector material, which is carried out in the following steps in sequence:

[0018] S1. The raw materials are prepared according to the alloy composition, and then added into a vacuum melting furnace. Argon is used as a protective gas. The temperature is increased from room temperature to 800-1000°C at a heating rate of 5-10°C / min, and the temperature is kept for 0.5-1h. After all the raw materials are melted, the temperature is reduced to 700-950°C at a cooling rate of 5-10°C / min, and the temperature is kept for 0.5-1h. After being taken out, the alloy is water-cooled to obtain alloy A-xB;

[0019] S2. Cut the A-xB cast alloy into a solid cylinder with a diameter of 50 mm and a height of 20 mm, and polish the surface with 2000 grit sandpaper;

[0020] S3, placing the alloy sample treated in step S2 into a pyrophyllite mold, and then placing it in a high-pressure six-sided top press for high-pressure solution treatment, taking out the alloy sample after cooling and washing it with anhydrous ethanol for 2-4 times;

[0021] S4. Use 2000-grit sandpaper to gently polish the surface of the alloy sample and wrap it evenly with carbon paper, then place it on the platform of a Joule heat treatment device and perform Joule heat treatment under an argon atmosphere. After cooling, take out the alloy sample and wash it 2-4 times with anhydrous ethanol to obtain a nano-twin alloy current collector material.

[0022] As a limitation of the preparation method of the present invention, in step S3, the pressure during the high-pressure solution treatment is 4-8 GPa, the temperature is 500-1200°C, the heating rate is 5-20°C / min, and the holding time is 30-60 min.

[0023] In the present invention, high pressure solution treatment provides a basis for subsequent Joule heat treatment. When the temperature is increased from room temperature to 500-1200°C at a heating rate of 5-20°C / min, the metal elements in the alloy raw materials diffuse with each other and form a solid solution at this stage; if the temperature is greater than 1200°C, the alloy will be overburned, phase separation and grain coarsening will occur; if the temperature is less than 500°C, the formation of the solid solution cannot be effectively promoted, resulting in the inability to optimize the performance of the alloy; if the heating rate is greater than 20°C / min, the elements in the alloy will diffuse unevenly, resulting in the alloy The uneven distribution of Si, Ag or Sn in the alloy, if the heating rate is less than 5℃ / min, the heating process will be too slow, forming larger grains, and the 30-60min heat preservation is to ensure the full implementation of the solid solution treatment, so that the Si, Ag or Sn elements in the alloy are completely diffused and form a uniform solid solution. If the heat preservation time is less than 30min, the solid solution treatment will be incomplete, and the Si, Ag, Sn elements that are not completely diffused will remain in the alloy, affecting the formation of a complete solid solution. If the heat preservation time is greater than 60min, it will cause the coarsening of the grains. The pressure is selected to be 4-8GPa because it will effectively promote the rapid diffusion between atoms in the alloy under this pressure, and the alloy solubility is larger in this pressure range, so that the alloy can form a more uniform metastable structure under high pressure, further improving its performance. If the pressure is greater than 8GPa, other phase changes will occur, affecting the stability of the alloy. If the pressure is less than 4GPa, it will not provide enough pressure to promote the diffusion between atoms, resulting in poor solid solution effect of the alloy.

[0024] As another limitation of the preparation method of the present invention, in step S4, the temperature of the Joule heat treatment is 800-1800° C. and the time is 50 ms-2 s.

[0025] In the present invention, Joule heat treatment, as an external stimulus for changing the free energy of the alloy system, can overcome the original thermal equilibrium state of the system and promote the occurrence of non-equilibrium entropy relaxation, thereby leading to the formation of a large number of crystal defects. When the treatment temperature is 800-1800°C, it will rapidly cause atomic diffusion in the alloy, promote the precipitation of nano-solute particles in the supersaturated solid solution, and contribute to the formation of nano-twin particles. If the treatment temperature is less than 800°C, sufficient atomic movement cannot be stimulated, resulting in failure to effectively generate a nano-twin structure in the alloy. If the treatment temperature is greater than 1800°C, it may cause excessive melting of the alloy, resulting in phase separation or grain coarsening, which in turn damages the structural stability of the alloy. The treatment of 50ms-2s is to rapidly change the structure of the alloy in a short time, promote the rapid generation of nano-twins, and avoid excessive coarsening or uneven distribution caused by long-term heat treatment. If the treatment time is less than 50ms, insufficient heat treatment will result, and atomic diffusion and twin formation in the alloy will not be fully stimulated. If the treatment time is greater than 2s, the grains will grow excessively, which will in turn affect the electrochemical properties and stability of the alloy.

[0026] In the present invention, high pressure solution treatment and Joule heat treatment process are complementary and indispensable key steps, wherein high pressure solution treatment provides a basis for Joule heat treatment, that is, by significantly improving the solubility and distribution uniformity of Si, Ag or Sn metal elements in the alloy, an optimized lattice structure and high energy state are provided for Joule heat treatment. After high pressure solution treatment, the lattice structure of the alloy is relatively unstable due to the rapid heating and high pressure environment in the high pressure solution process, and the arrangement and distribution of the internal atoms are relatively unstable, and the alloy is in a non-equilibrium state of high energy and supersaturation of solute, which provides favorable conditions for Joule heat treatment, so that in the Joule heat treatment process, the supersaturated solid solution alloy can more easily undergo structural changes and be transformed into a more stable form, especially the formation of nano twin structure. Due to the unstable arrangement of atoms in the high energy state, they can be quickly rearranged under external thermal stimulation, thereby promoting the generation of twins, and therefore, the alloy is in a metastable and high energy state, making Joule heat treatment a key step in activating the formation of nano twins. In addition, during the instantaneous high temperature effect and rapid cooling of the alloy, the Si, Ag or Sn elements in the alloy are rapidly precipitated in a short time, and the Si, Ag or Sn atoms undergo rapid rearrangement and are in a non-equilibrium state. Since the twin defect formation energy in the lattice is the lowest under high temperature conditions, Si, Ag or Sn atoms will preferentially form a large number of twins under this condition. Joule heat treatment can stimulate a large number of nano twins in a very short time by heating the alloy to a high temperature and rapidly cooling it. This process not only ensures the high density and uniformity of the twins, but also significantly changes the microstructure of the alloy, thereby greatly improving its mechanical properties. The twin structure generated after Joule heat treatment can also effectively relieve the stress caused by volume changes during the battery charging and discharging process, which helps to improve the battery's cycle stability.

[0027] The above technical solution of the present invention is taken as a whole, and each step is closely related and influences each other, which jointly determine the morphological characteristics and performance of the product.

[0028] The above technical solution has the following advantages or beneficial effects:

[0029] 1. The nanoparticles containing twin defects in the nano-twin alloy current collector prepared by the present invention account for 65-85% of the total nanoparticles, which can significantly increase the diffusion rate of the metal on the current collector surface, thereby improving the uniformity of metal deposition, avoiding the growth of metal dendrites, and preventing the potential safety hazards caused by piercing the battery separator due to uneven deposition, thereby improving the cycle stability and safety of the battery;

[0030] 2. After the nano-twin alloy current collector material prepared by the present invention is assembled into a full battery, the battery has excellent electrochemical performance and still has a high reversible capacity after a long cycle;

[0031] 3. The preparation method of the present invention is simple, the process is easy to control, and the production cycle is short, which is suitable for large-scale industrial production.

[0032] The invention is suitable for preparing nano twin alloy current collector materials.

[0033] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a scanning electron microscope image of the Cu-15wt.%Ag alloy prepared in Example 1 of the present invention after high pressure solution treatment;

[0035] Figure 2 This is a transmission electron microscope image of the Cu-15wt.%Ag nano-twin alloy prepared in Example 1 of the present invention;

[0036] Figure 3 This is a scanning electron microscope image of the Cu-15wt.%Ag nano-twin alloy current collector prepared in Example 1 of the present invention after calcium is deposited on the surface;

[0037] Figure 4 This is a transmission electron microscope image of the Ni-12wt.% Sn nanotwin alloy prepared in Example 2 of the present invention;

[0038] Figure 5 This is a scanning electron microscope image of the Ni-12wt.%Sn nano-twin alloy current collector prepared in Example 2 of the present invention after potassium is deposited on the surface;

[0039] Figure 6This is a transmission electron microscope image of the Al-10wt.%Si nano-twin alloy prepared in Example 3 of the present invention;

[0040] Figure 7 This is a scanning electron microscope image of the Al-10wt.% Si nano-twin alloy current collector prepared in Example 3 of the present invention after magnesium is deposited on the surface;

[0041] Figure 8 This is a transmission electron microscope image of the Al-12wt.%Si nano-twin alloy prepared in Example 4 of the present invention;

[0042] Fig. 9 This is a scanning electron microscope image of the Al-12wt.%Si nano-twin alloy current collector prepared in Example 4 of the present invention after sodium is deposited on the surface;

[0043] Fig.10 This is a performance test diagram of a sodium full battery assembled with the Al-12wt.% Si nano-twin alloy current collector prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0044] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.

[0045] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry, wherein the high-pressure six-sided top press is the CS-1B model produced by Xianyang Superhard Materials Equipment Co., Ltd., and the Joule heat treatment device is the JH-2023A model produced by Jilin Padick Precision Instrument Co., Ltd.

[0046] The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.

[0047] Example 1

[0048] This embodiment prepares a nano twin alloy current collector material, the chemical expression of which is Cu-15wt.%Ag, and the preparation process and steps are as follows:

[0049] S1. The raw materials are prepared according to the alloy composition, and then added into a vacuum melting furnace, argon is used as a protective gas, the temperature is increased from room temperature to 1000°C at a heating rate of 10°C / min, and the temperature is kept for 1 hour. After all the raw materials are melted, the temperature is reduced to 950°C at a cooling rate of 10°C / min, and the temperature is kept for 1 hour. After being taken out, the alloy Cu-15wt.%Ag is obtained by water cooling;

[0050] S2. Cut the Cu-15wt.%Ag cast alloy into a solid cylinder with a diameter of 50 mm and a height of 20 mm, and use 2000-grit sandpaper to polish the surface to remove oxides;

[0051] S3, the alloy sample treated in step S2 is loaded into a pyrophyllite mold, and placed in the cavity of a high-pressure six-sided top press, and high-pressure treatment is performed after the hammer head is calibrated; the pressure system is started to increase the pressure to 8GPa, and then the temperature is increased from room temperature to 1200°C at a heating rate of 20°C / min, and the temperature is kept for 60min. After the insulation is completed, the power is turned off to stop heating, and the circulating water system is immediately started to quickly cool to room temperature, and after taking out, it is washed twice with anhydrous ethanol;

[0052] S4. Use 2000 mesh sandpaper to gently polish the surface of the alloy sample and wrap it evenly with carbon paper, then place it on the platform of the Joule heat treatment device and treat it at 1800°C for 2s in an argon atmosphere. After the treatment, immediately turn off the power and start the liquid nitrogen cooling system to quickly cool the alloy sample to room temperature, then take it out and wash it twice with anhydrous ethanol to obtain a Cu-15wt.%Ag nano-twin alloy current collector, in which nanoparticles containing twin defects account for 65% of the total nanoparticles.

[0053] The nano twin alloy prepared in this example was characterized. Figure 1 , is a scanning electron microscope image of Cu-15wt.%Ag after high-pressure solution treatment. It can be seen from the figure that after high-pressure solution treatment, there is no Ag particle enrichment inside the alloy of Cu-15wt.%Ag, indicating that the high-pressure treatment completely dissolves Ag into the matrix without forming separate particles or enriched areas. This indicates that the Ag element has been completely integrated into the alloy matrix rather than existing alone in the alloy, further confirming that high-pressure solution treatment significantly improves the alloy structure uniformity and element solubility.

[0054] like Figure 2 , is a transmission electron microscope image of the Cu-15wt.% Ag nano-twin alloy prepared in this embodiment. It can be seen from the figure that after high-pressure solid solution and Joule heat treatment, nano-twin Ag particles are evenly distributed inside the Cu-15wt.% Ag alloy. The size of the twin particles is 40nm, accounting for 65% of the total nanoparticles, indicating that the method of combining high-pressure solid solution with Joule heat treatment can produce a large number of nano-twins.

[0055] The Cu-15wt.% Ag nano-twin alloy prepared in this embodiment was used as the negative electrode current collector, 1M Ca[B(hfip)4]2in DME=100vol% was selected as the electrolyte, a polyethylene diaphragm was selected as the separator, and expanded graphite carbon was selected as the positive electrode material. The calcium metal battery was assembled in a glove box, and the performance of the assembled battery was tested using a blue battery test system and an electrochemical workstation.

[0056] like Figure 3 , is a scanning electron microscope image of the Cu-15wt.% Ag nano-twin alloy current collector prepared in this embodiment after calcium is deposited on the surface. It can be seen from the figure that the surface of the Cu-15wt.% Ag nano-twin alloy current collector presents a smooth and dense calcium deposition morphology, and no dendrite growth occurs; in addition, the assembled calcium metal full battery can stably cycle 300 times within the voltage range of 2.0V-4.5V and the current density of 100mA / g, and the discharge specific capacity after cycling is 90mAh / g.

[0057] Example 2

[0058] This embodiment prepares a nano twin alloy current collector material, the chemical expression of which is Ni-12wt.%Sn, and the preparation process and steps are as follows:

[0059] S1. The raw materials are prepared according to the alloy composition, and then added into a vacuum melting furnace, argon is used as a protective gas, the temperature is increased from room temperature to 900°C at a heating rate of 10°C / min, and the temperature is kept for 1 hour. After all the raw materials are melted, the temperature is reduced to 850°C at a cooling rate of 10°C / min, and the temperature is kept static for 1 hour. After being taken out, the alloy Ni-12wt.%Sn is obtained by water cooling;

[0060] S2. Cut the Ni-12wt.%Sn cast alloy into a solid cylinder with a diameter of 50 mm and a height of 20 mm, and use 2000-grit sandpaper to polish the surface to remove oxides;

[0061] S3, the alloy sample treated in step S2 is loaded into a pyrophyllite mold, and placed in the cavity of a high-pressure six-sided top press, and high-pressure treatment is performed after the hammer head is calibrated; the pressure system is started to increase the pressure to 6GPa, and then the temperature is increased from room temperature to 800°C at a heating rate of 10°C / min, and the temperature is kept for 45min. After the insulation is completed, the power is turned off to stop heating, and the circulating water system is immediately started to quickly cool to room temperature, and after taking out, it is washed 3 times with anhydrous ethanol;

[0062] S4. Use 2000 mesh sandpaper to gently polish the surface of the alloy sample and wrap it evenly with carbon paper, then place it on the platform of the Joule heat treatment device and treat it at 1200°C for 1 second under argon atmosphere. After the treatment, immediately turn off the power and start the liquid nitrogen cooling system to quickly cool the alloy sample to room temperature, then take it out and wash it 3 times with anhydrous ethanol to obtain a Ni-12wt.%Sn nanotwin alloy current collector, in which nanoparticles containing twin defects account for 70% of the total nanoparticles.

[0063] The nano twin alloy prepared in this example was characterized. Figure 4 , is a transmission electron microscope image of the Ni-12wt.% Sn nano-twin alloy prepared in this embodiment. It can be seen from the figure that after high-pressure solid solution and Joule heat treatment, nano-twin Sn particles are evenly distributed inside the Ni-12wt.% Sn alloy. The size of the twin particles is 40nm, accounting for 70% of the total nanoparticles, indicating that the method of combining high-pressure solid solution with Joule heat treatment can produce a large number of nano-twins.

[0064] The Ni-12wt.% Sn nanotwin alloy prepared in this example was used as the negative electrode current collector, 2M KFSI in PC=100vol% was selected as the electrolyte, polyethylene diaphragm was selected as the separator, and perylenetetracarboxylic dianhydride was selected as the positive electrode material. The potassium metal battery was assembled in a glove box. The performance of the assembled battery was tested using a blue battery test system and an electrochemical workstation.

[0065] like Figure 5 , is a scanning electron microscope image of the Ni-12wt.% Sn nano-twin alloy current collector prepared in this embodiment after potassium is deposited on the surface. It can be seen from the figure that the surface of the Ni-12wt.% Sn nano-twin alloy current collector presents a smooth and dense potassium deposition morphology, and no dendrite growth occurs. In addition, the assembled potassium metal full battery can stably cycle 200 times within the voltage range of 2.0V-4.0V and the current density of 100mA / g, and the discharge specific capacity after cycling is 120mAh / g.

[0066] Example 3

[0067] This embodiment prepares a nano twin alloy current collector material, the chemical expression of which is Al-10wt.%Si, and the preparation process and steps are as follows:

[0068] S1. The raw materials are prepared according to the alloy composition, and then added into a vacuum melting furnace. Argon is used as a protective gas. The temperature is increased from room temperature to 800°C at a heating rate of 5°C / min, and the temperature is kept for 0.5h. After all the raw materials are melted, the temperature is reduced to 700°C at a cooling rate of 5°C / min, and the temperature is kept static for 0.5h. After being taken out, the alloy Al-10wt.%Si is obtained by water cooling.

[0069] S2, cutting the Al-10wt.%Si cast alloy into a solid cylinder with a diameter of 50 mm and a height of 20 mm, and using 2000-grit sandpaper to polish the surface to remove oxides;

[0070] S3, the alloy sample treated in step S2 is loaded into a pyrophyllite mold, and placed in the cavity of a high-pressure six-sided top press, and high-pressure treatment is performed after the hammer head is calibrated; the pressure system is started to increase the pressure to 4 GPa, and then the temperature is increased from room temperature to 500 ° C at a heating rate of 5 ° C / min, and the temperature is kept for 30 minutes. After the insulation is completed, the power is turned off to stop heating, and the circulating water system is immediately started to quickly cool to room temperature, and after taking out, it is washed 4 times with anhydrous ethanol;

[0071] S4. Use 2000 mesh sandpaper to gently polish the surface of the alloy sample and wrap it evenly with carbon paper, then place it on the platform of the Joule heat treatment device and treat it at 800°C for 50ms in an argon atmosphere. After the treatment, immediately turn off the power and start the liquid nitrogen cooling system to quickly cool the alloy sample to room temperature, then take it out and wash it 4 times with anhydrous ethanol to obtain an Al-10wt.%Si nanotwin alloy current collector, in which nanoparticles containing twin defects account for 85% of the total nanoparticles.

[0072] The nano twin alloy prepared in this example was characterized. Figure 6 , is a transmission electron microscope image of the Al-10wt.% Si nano-twin alloy prepared in this embodiment. It can be seen from the figure that after high-pressure solid solution and Joule heat treatment, nano-twin Si particles are evenly distributed inside the Al-10wt.% Si alloy. The size of the twin particles is 40nm, accounting for 85% of the total nanoparticles, indicating that the method of combining high-pressure solid solution with Joule heat treatment can produce a large number of nano-twins.

[0073] The Al-10wt.% Si nanotwin alloy prepared in this example was used as the negative electrode current collector, 1M Mg(TFSI)2in THF=100vol% was selected as the electrolyte, glass fiber separator was selected as the separator, and Mo6S8 was selected as the positive electrode material. The magnesium metal battery was assembled in the glove box. The performance of the assembled battery was tested using the Blue Battery Test System and the electrochemical workstation.

[0074] like Figure 7, is a scanning electron microscope image of the Al-10wt.% Si nano-twin alloy current collector prepared in this embodiment after magnesium is deposited on the surface. It can be seen from the figure that metallic magnesium is uniformly deposited on the Al-10wt.% Si nano-twin alloy current collector, and no dendrite growth occurs, indicating that the Al-10wt.% Si nano-twin alloy current collector can inhibit the uneven deposition of metal. In addition, the assembled magnesium metal full battery can stably cycle 100 times within the voltage range of 0.2V-2.0V and the current density of 50mA / g, and the discharge specific capacity after cycling is 60mAh / g.

[0075] Example 4

[0076] This embodiment prepares a nano twin alloy current collector material, the chemical expression of which is Al-12wt.%Si, and the preparation process and steps are as follows:

[0077] S1. The raw materials are prepared according to the alloy composition, and then added into a vacuum melting furnace, argon is used as a protective gas, the temperature is increased from room temperature to 800°C at a heating rate of 8°C / min, and the temperature is kept for 0.7h. After all the raw materials are melted, the temperature is reduced to 700°C at a cooling rate of 8°C / min, and the temperature is kept static for 0.7h. After being taken out, the alloy Al-12wt.%Si is obtained by water cooling;

[0078] S2. Cut the Al-12wt.%Si cast alloy into a solid cylinder with a diameter of 50 mm and a height of 20 mm, and use 2000-grit sandpaper to polish the surface to remove oxides;

[0079] S3, the alloy sample treated in step S2 is loaded into a pyrophyllite mold, and placed in the cavity of a high-pressure six-sided top press, and high-pressure treatment is performed after the hammer head is calibrated; the pressure system is started to increase the pressure to 5GPa, and then the temperature is increased from room temperature to 700°C at a heating rate of 10°C / min, and the temperature is kept for 30min. After the insulation is completed, the power is turned off to stop heating, and the circulating water system is immediately started to quickly cool to room temperature, and after taking out, it is washed 3 times with anhydrous ethanol;

[0080] S4. Use 2000 mesh sandpaper to gently polish the surface of the alloy sample and wrap it evenly with carbon paper, then place it on the platform of the Joule heat treatment device, and treat it at 1000°C for 100ms in an argon atmosphere. After the treatment, immediately turn off the power and start the liquid nitrogen cooling system to quickly cool the sample to room temperature and then take it out and wash it 3 times with anhydrous ethanol to obtain an Al-12wt.%Si nanotwin alloy current collector, in which nanoparticles containing twin defects account for 80% of the total nanoparticles.

[0081] The nano twin alloy prepared in this example was characterized. Figure 8, is a transmission electron microscope image of the Al-12wt.% Si nano-twin alloy prepared in this embodiment. It can be seen from the figure that after high-pressure solid solution and Joule heat treatment, the Al-12wt.% Si alloy has uniformly distributed nano-twin Si particles inside the alloy. The size of the twin particles is 40nm, accounting for 80% of the total nano-particles, indicating that the method of combining high-pressure solid solution with Joule heat treatment can produce a large number of nano-twins.

[0082] The Al-12wt.% Si nanotwin alloy prepared in this example was used as the negative electrode current collector, 1M NaPF6 in DIGLYME=100vol% was selected as the electrolyte, a polyethylene diaphragm was selected as the separator, and sodium vanadium phosphate was selected as the positive electrode material. The sodium metal battery was assembled in a glove box. The performance of the assembled battery was tested using a blue battery test system and an electrochemical workstation.

[0083] like Fig. 9 , is a scanning electron microscope image of the Al-12wt.%Si nano-twin alloy current collector surface after sodium deposition obtained in this embodiment. It can be seen from the figure that the surface of the Al-12wt.%Si nano-twin alloy current collector presents a smooth and dense sodium deposition morphology, and no dendrite growth occurs; in addition, Fig.10 , is a performance test diagram of the Al-12wt.% Si nano-twin alloy current collector prepared in this embodiment after assembling a sodium full battery. It can be seen from the figure that the assembled sodium metal full battery can stably cycle 200 times within the voltage range of 2.5V-3.8V and the current density of 100mA / g, and the discharge specific capacity after the cycle is 127mAh / g.

[0084] Comparative Example

[0085] In order to explore the influence of different preparation steps in the preparation process of the present invention on the performance of the product of the present invention, the following comparative experiments were carried out. Different alloy current collector materials were prepared in the following comparative examples, as follows:

[0086] Comparative Example 1

[0087] In this comparative example, an alloy current collector material is prepared. The preparation process is similar to that of Example 4, except that only step S1 is performed, and the high-temperature solution treatment and Joule heat treatment of steps S2, S3 and S4 are not performed.

[0088] Comparative Example 2

[0089] In this comparative example, an alloy current collector material is prepared. The preparation process is similar to that of Example 4, except that the Joule heat treatment in step S4 is not performed, but a low-temperature aging treatment is used, i.e., low-temperature aging at 180°C for 2h. The remaining steps and parameters are the same as those of Example 4.

[0090] Comparative Example 3

[0091] In this comparative example, an alloy current collector material is prepared. The preparation process is similar to that of Example 4, except that in step S3, the solid solution condition is to increase the temperature from room temperature to 700°C at a heating rate of 2°C / min, keep the temperature for 20 minutes, and no pressure is applied. The steps and parameters are the same as those of Example 4.

[0092] Comparative Example 4

[0093] In this comparative example, the alloy current collector material is prepared according to the steps and methods disclosed in Chinese invention patent application No. 201410613914.5, and the Cu-Al nano-twin alloy material is prepared through multiple processes such as solid solution, cooling, isochannel deformation, and cryogenic treatment.

[0094] The alloy current collector materials prepared in Comparative Examples 1-4 were assembled into button-type sodium metal batteries, with 1M NaPF6 in DIGLYME = 100 vol% as the electrolyte, a polyethylene diaphragm as the separator, and sodium vanadium phosphate as the positive electrode material. The sodium metal batteries were assembled in a glove box, and the performance of the assembled batteries was tested using a blue battery test system and an electrochemical workstation. The specific test results are as follows:

[0095]

[0096] As can be seen from the above table, in Comparative Examples 1-3, since there are only a small amount of or even no nano twins in the prepared alloy current collector material, the deposition uniformity of the metal on the current collector surface in the metal battery is poor, which ultimately leads to poor cycle stability of the metal full battery. Although the alloy current collector material prepared in Comparative Example 4 contains a large number of nano twins, the presence of the lamellar structure causes the metal to be deposited along the twin defects at the lamellar layer, thereby forming a linear metal deposition. As the battery capacity increases, the deposition process tends to become uneven, thereby reducing the overall performance of the battery. The nano twin particles precipitated from the nano twin alloy current collector material prepared by the present invention are evenly distributed in the alloy matrix, forming a more compact and uniform microstructure, so that the metal can be deposited more evenly on the current collector surface, avoiding the formation of dendrites, thereby improving the battery's cycle stability and capacity retention rate.

[0097] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.

Claims

1. A nano twin alloy current collector material, characterized in that: The chemical composition expression is: A-xB, wherein A is one of Al, Cu or Ni, and B is one of Si, Ag or Sn; x is the mass fraction of component B, ranging from 10-15wt.%.

2. A nano twin alloy current collector material according to claim 1, characterized in that: In the nano-twin alloy current collector material, nanoparticles containing twin defects account for 65-85% of the entire nanoparticles.

3. The method for preparing a nano-twin alloy current collector material according to claim 1 or 2, characterized in that: Follow the steps below in order: S1. The raw materials are prepared according to the alloy composition, and then added into a vacuum melting furnace. Argon is used as a protective gas. The temperature is increased from room temperature to 800-1000°C at a heating rate of 5-10°C / min, and the temperature is kept for 0.5-1h. After all the raw materials are melted, the temperature is reduced to 700-950°C at a cooling rate of 5-10°C / min, and the temperature is kept for 0.5-1h. After being taken out, the alloy is water-cooled to obtain alloy A-xB; S2. Cut the A-xB alloy into a solid cylinder with a diameter of 50 mm and a height of 20 mm, and polish the surface cleanly with 2000-grit sandpaper; S3, placing the alloy sample treated in step S2 into a pyrophyllite mold, and then placing it in a high-pressure six-sided top press for high-pressure solution treatment, taking out the alloy sample after cooling and washing it with anhydrous ethanol for 2-4 times; S4. Use 2000-grit sandpaper to gently polish the surface of the alloy sample and wrap it evenly with carbon paper, then place it on the platform of a Joule heat treatment device and perform Joule heat treatment under an argon atmosphere. After cooling, take out the alloy sample and wash it 2-4 times with anhydrous ethanol to obtain a nano-twin alloy current collector material.

4. The method for preparing a nano-twin alloy current collector material according to claim 3, characterized in that: In step S3, the pressure during the high-pressure solution treatment is 4-8 GPa, the temperature is 500-1200° C., the heating rate is 5-20° C. / min, and the holding time is 30-60 min.

5. The method for preparing a nano-twin alloy current collector material according to claim 3, characterized in that: In step S4, the Joule heat treatment is performed at a temperature of 800-1800° C. and a time of 50 ms-2 s.

Citation Information

Patent Citations

  • Method for preparing nano-sized twin crystal Cu-Al or Cu-Zn alloy

    CN104451486A

  • Three-dimensional porous current collector as well as preparation method and use thereof

    CN104716330A